2017
DOI: 10.3892/or.2017.5380
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression profiles of non-small cell lung cancer at different stages reveals significantly altered biological functions and candidate genes

Abstract: We attempt to dissect the pathology of non-small cell lung cancer (NSCLC) patients at different stages and discover the novel candidate genes. Microarray data (GSE21933) were retrieved from the Gene Expression Omnibus database. The differential expression profiles of lung tumor tissues during different stages were analyzed. The significantly altered functions and pathways were assessed and the key nodes in a protein-protein interaction (PPI) network were screened out. Then, the coexpression gene pairs and tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
14
1
Order By: Relevance
“…Hence, it is essential to investigate the biological characteristics of CRC further, as well as develop new biomarkers for the stratification of patients with CRC into different prognostic subgroups to improve treatment decision-making for CRC. LBX2 is located on chromosome 2p13.1 and several previous studies have reported that it is dysregulated in non-small cell lung cancer, adenoid cystic carcinoma and T-cell acute lymphoblastic leukemia (11)(12)(13). However, the expression levels of LBX2 and its clinical significance in CRC has not been investigated before, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Hence, it is essential to investigate the biological characteristics of CRC further, as well as develop new biomarkers for the stratification of patients with CRC into different prognostic subgroups to improve treatment decision-making for CRC. LBX2 is located on chromosome 2p13.1 and several previous studies have reported that it is dysregulated in non-small cell lung cancer, adenoid cystic carcinoma and T-cell acute lymphoblastic leukemia (11)(12)(13). However, the expression levels of LBX2 and its clinical significance in CRC has not been investigated before, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 92%
“…The underlying mechanisms of LBX2 upregulation in CRC were further explored. LBX2 is located on chromosome 2p13.1, which has been identified differentially expressed in several malignancies (11)(12)(13). From the perspective of genetic and epigenetic alterations, it was demonstrated that 88 patients with CRC had low-level LBX2 DNA amplification, but this was not significantly correlated with LBX2 expression levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study also suggested that differential genera of microbiome existed in different histologic types and metastasis conditions of bronchial washing uid (BWF) and sputum specimens from lung cancer patients [9]. Furthermore, many researchers have demonstrated that the biological patterns, genomic signatures as well as metastasis mechanisms are differential in various clinicopathology of lung cancer [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, gene expression analysis-based microarray was widely used to study the NSCLC, and hundreds of differentially expressed genes (DEGs) were found by differentially expressed gene analysis (DEGA) (4)(5)(6). Furthermore, several key genes, including the well-known gene epidermal growth factor receptor (EGFR) and tumor protein p53 (TP53) were identified (5).…”
Section: Introductionmentioning
confidence: 99%